Nunalleq Digital Museum - Anderson, John; Hillerdal, Charlotta; Watterson, Alice; Cleveland, Jacqueline Nalikutaar; Strunk, Lonny Alaskuk; Mossolova, Anna; Knecht, Rick (University of Aberdeen, 2023)
The Nunalleq Digital Museum is an online resource that can be used to explore the archaeological collection and current interpretation from excavations of a pre-contact Yup'ik village. Co-curated by the local community in Quinhagak, Alaska, the resource brings together a rich collection of voices and insights to explore the Yup'ik past and present. The Nunalleq Digital Museum comprises a digital Exhibition and Catalogue. In the Exhibition section visitors will encounter material from the archaeological excavations of a 16th century Yup'ik village, located on the Bering Sea coast a few miles from the modern-day village of Quinhagak, Alaska. Through artists reconstructions, 3D scans of the collections and insights from a variety of voices this resource will help you to imagine what life in a Yup'ik village was like in the past, at a time before the Euro-American colonisation of Alaska. You can also search the Catalogue where 6,000 of the over 100,000 objects found in the excavations are available with pictures and interpretive information.